An inhibitor of interaction between the transcription factor NRF2 and the E3 ubiquitin ligase adapter β-TrCP delivers anti-inflammatory responses in mouse liver - Raquel Fernández-Ginés; José Antonio Encinar; John D. Hayes; Baldo Oliva; Maria Isabel Rodríguez-Franco; Ana I. Rojo; Antonio Cuadrado (Redox Biology, 2022)
It is widely accepted that activating the transcription factor NRF2 will blast the physiological anti-inflammatory mechanisms, which will help combat pathologic inflammation. Much effort is being put in inhibiting the main NRF2 repressor, KEAP1, with either electrophilic small molecules or disrupters of the KEAP1/NRF2 interaction. However, targeting β-TrCP, the non-canonical repressor of NRF2, has not been considered yet. After in silico screening of ∼1 million compounds, we now describe a novel small molecule, PHAR, that selectively inhibits the interaction between β-TrCP and the phosphodegron in transcription factor NRF2. PHAR upregulates NRF2-target genes such as Hmox1, Nqo1, Gclc, Gclm and Aox1, in a KEAP1-independent, but β-TrCP dependent manner, breaks the β-TrCP/NRF2 interaction in the cell nucleus, and inhibits the β-TrCP-mediated in vitro ubiquitination of NRF2. PHAR attenuates hydrogen peroxide induced oxidative stress and, in lipopolysaccharide-treated macrophages, it downregulates the expression of inflammatory genes Il1b, Il6, Cox2, Nos2. In mice, PHAR selectively targets the liver and greatly attenuates LPS-induced liver inflammation as indicated by a reduction in the gene expression of the inflammatory cytokines Il1b, TNf, and Il6, and in F4/80-stained liver resident macrophages. Thus, PHAR offers a still unexplored alternative to current NRF2 activators by acting as a β-TrCP/NRF2 interaction inhibitor that may have a therapeutic value against undesirable inflammation.